2012
DOI: 10.4314/thrb.v14i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric injuries among patients attending a regional hospital in Shinyanga Tanzania

Abstract: Geriatric injuries pose a major challenge to surgeons and general practitioners in developing countries. The objective of this study was to determine the prevalence, injury characteristics and outcomes of geriatric injury among patients at Shinyanga Regional Hospital in Tanzania. Data was collected using a pre-tested, coded questionnaire and analyzed using SPSS computer system. A total of 94 geriatric trauma patients constituting 22.7% of all trauma admissions were studied. The male to female ratio was 1.4:1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Saidi et al showed similar patterns of injury to our study with a comparable percent of elderly patients in their trauma population (4.5 vs. our 2.9 %) [11]. Chalya et al had different findings in neighboring Tanzania, where nearly 25 % of all patients were 60 years or older [12], They also had a very high rate of assault (52.1 vs. our 13.6 %) with an associated increase in upper extremity injuries. Their high assault rate compared to our study and Saidi's report is likely explained by local socioeconomic factors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Saidi et al showed similar patterns of injury to our study with a comparable percent of elderly patients in their trauma population (4.5 vs. our 2.9 %) [11]. Chalya et al had different findings in neighboring Tanzania, where nearly 25 % of all patients were 60 years or older [12], They also had a very high rate of assault (52.1 vs. our 13.6 %) with an associated increase in upper extremity injuries. Their high assault rate compared to our study and Saidi's report is likely explained by local socioeconomic factors.…”
Section: Discussionsupporting
confidence: 81%
“…There is a paucity of data on the characteristics and outcomes of the elderly trauma patient in sub-Saharan Africa. A few studies have been published, mostly with very small cohorts of elderly patients and most without comparison to younger patients [11][12][13][14][15]. The most relevant studies were from neighboring Tanzania and Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geriatric trauma, most commonly defined as trauma affecting patients aged 65 and older, is an emerging global problem [ 1 , 2 ]. Elderly trauma patients suffer increased morbidity and mortality that can be attributed to age, pre-existing disease, complications, injury severity, and their unique physiology, behavior, and anatomy [ 3 , 4 ]. Consequently, medical and surgical resource needs for their injuries are disproportionately greater than for the same injuries in younger patients [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, medical and surgical resource needs for their injuries are disproportionately greater than for the same injuries in younger patients [5] . Outcomes of geriatric trauma patients may be especially poor in developing countries, where the lack of advanced pre-hospital care systems and trauma centres hinder optimal trauma care [ 3 , 4 , 6 ]. Existing studies on trauma in Malawi have found increased mortality among elderly patients compared to.…”
Section: Introductionmentioning
confidence: 99%